Integrating Linguistics Theories in Developing Foreign Language Teaching Materials (German Grammar Textbook for Indonesian Learners) - R, Mantasiah; Yusri, Yusri; Anwar, Muhammad; Hasmawati, Hasmawati (International Journal of Language Education, 2021)
This study aims to investigate the effectiveness of German grammar textbook using linguistic approaches in increasing students’ academic motivation, learning outcome, and linguistic understanding. This German grammar textbook is composed for Indonesian learners. This study employed experimental approach by involving two experimental groups without control group. The total research participants were 45 Indonesian students in the second semester of the German language education department divided into two classes. There were three variables observed in this study. Students’ learning outcome was measured by a grammar test developed by the researchers, while students’ academic motivation was measured using a scale developed by Vallerand et al. (1992) consisting of 28 items that had been translated into Indonesian and tested by Natalya & Purwanto (2018). Students’ linguistic understanding was measured using the linguistic understanding scale developed by Hasmawati (2021). The treatment was conducted in six meetings in which each meeting took place for two hours using Zoom video conference platform. Data were analyzed using a descriptive statistic, a correlation test, and a paired sample t-test using the SPSS-26 application. The study found that the integration of linguistic approach, error analysis and contrastive analysis, in composing a grammar textbook of a foreign language is more likely to positively affect students’ academic motivation, learning outcome, and linguistic understanding.